A Case of Thrombotic Thrombocytopenia Purpura Associated with Systemic Lupus Erythematosus: Diagnostic Utility of ADAMTS-13 Activity. (15th June 2011) - Yamada, Risa; Nozawa, Kazuhisa; Yoshimine, Takashi; Takasaki, Yoshinari; Ogawa, Hideoki; Takamori, Kenji; Sekigawa, Iwao
Abstract : Thrombotic thrombocytopenia purpura (TTP) caused by a deficiency in ADAMTS-13 activity is considered to involve a subset of thrombotic microangiopathy (TMA). Although concept of TTP is included under the umbrella of TMA, discrimination of TTP from TMA is occasionally difficult in an autoimmune disorder. Herein, we report a case with TTP associated with systemic lupus erythematosus (SLE). In this case, it was difficult to discriminate TTP from TMA and the measurement of ADAMTS-13 activity was useful for obtaining an accurate diagnosis. SLE patients having thrombocytopenia in complication with anemia should be considered a monitoring of ADAMTS-13 activity even though the patients lacked symptoms of TTP related to the microvascular coagulation.